A large electrochemical setup for the anodization of aluminum towards highly ordered arrays of cylindrical nanopores - Assaud, Loic; Bochmann, Sebastian; Christiansen, Silke; Bachmann, Julien (Review of Scientific Instruments, 2015)
A new electrochemical setup and the associated procedures for growing ordered anodic aluminum oxide pore arrays on large surfaces are presented. The typical size of the samples is 14 x 14 cm(2). The most crucial experimental parameters that allow for the stabilization of the high-field procedures are a very efficient cooling of sample and electrolyte, as well as the initial ramping up of the voltage at an accurately defined rate. The morphology of the cylindrical, parallel alumina pores is similar to those obtained on smaller scales with standard setups. Our setup facilitates the availability of porous anodic alumina as a template system for a number of applications. (C) 2015 AIP Publishing LLC.

An electrochemically functional layer of hydrogenase extract on an electrode of large and tunable specific surface area - Schlicht, Stefanie; Assaud, Loic; Hansen, Moritz; Licklederer, Markus; Bechelany, Mikhael; Perner, Mirjam; Bachmann, Julien (Journal of Materials Chemistry A, 2016)
Electrode supports are generated by electrospinning of polyacrylonitrile fibers and subsequent coating of a thin electrically conductive TiO2 layer by atomic layer deposition. The supports are then functionalized with a [NiFe]-hydrogenase-containing membrane fraction from Escherichia coli and are characterized structurally and electrochemically. The hydrogenase suspension generates a micron-thick organic film around the fiber mat, which exhibits electrocatalytic activity for hydrogen evolution. Furthermore, the electrode geometric surface area is varied systematically via the electrospinning procedure, which reduces the charge transfer resistance and increases the hydrogen evolution current density to > 500 mu A cm(-2) at 0.3 V overpotential.

Antimony sulfide as a light absorber in highly ordered, coaxial nanocylindrical arrays: preparation and integration into a photovoltaic device - Wu, Yanlin; Assaud, Loic; Kryschi, Carola; Capon, Boris; Detavernier, Christophe; Santinacci, Lionel; Bachmann, Julien (Journal of Materials Chemistry A, 2015)
We demonstrate the preparation of functional 'extremely thin absorber' solar cells consisting of massively parallel arrays of nanocylindrical, coaxial n-TiO2/i-Sb2S3/p-CuSCN junctions. Anodic alumina is used as an inert template that provides ordered pores of 80 nm diameter and 1-50 mu m length. Atomic layer deposition (ALD) then coats pores of up to 20 mm with thin layers of the electron conductor and the intrinsic light absorber. The crystallization of the initially amorphous Sb2S3 upon annealing is strongly promoted by an underlying crystalline TiO2 layer. After the remaining pore volume is filled with the hole conductor by solution evaporation, the resulting coaxial p-i-n junctions display stable diode and photodiode electrical characteristics. A recombination timescale of 40 ms is extracted from impedance spectroscopy in open circuit conditions, whereas transient absorption spectroscopy indicates that holes are extracted from Sb2S3 with a lifetime of 1 ns.

Atomic Layer Deposition of i-Sb2S3/p-NiO Thin Layers into Anodic Alumina Membranes for Photoelectrochemical Water Splitting - Barr, M. K.S.; Assaud, Loic; Wu, Yanlin; Bachmann, Julien; Santinacci, L. (ECS Transactions, 2015)
A nanostructured photoelectrode was fabricated by atomic layer deposition (ALD) of NiO and Sb2S3 in nanoporous alumina. The fabrication, i.e. the successive ALD of NiO and Sb2S3, and the characterization of the arrays of coaxial NiO/Sb2S3 junction by electron microscopies are first reported. The optical and photoelectrochemical preliminary testing of the combination of such extremely thin absorber, Sb2S3, with a p-type semiconductor, NiO, are proposed in a second part. Although the photoconversion performances should be improved, the present work demonstrates validity of the concept.
EAM Import::2019-03-13

Engineering a three-dimensional, photoelectrochemically active p-NiO/i-Sb2S3 junction by atomic layer deposition - Barr, Maissa K. S.; Assaud, Loic; Wu, Yanlin; Laffon, Carine; Parent, Philippe; Bachmann, Julien; Santinacci, Lionel (Electrochimica Acta, 2015)
A p-NiO/i-Sb2S3 semiconductor junction is created as an array of parallel, coaxially structured, hollow nanocylinders. The preparation bases on two consecutive steps of atomic layer deposition (ALD) onto the pore walls of anodic alumina, used as an inert template. ALD allows for the conformal coating of the deep pores. Characterization by x-ray photoelectron spectroscopy, x-ray diffraction, and transmission electron microscopy demonstrates the high purity, perfect stoichiometry, and nanocrystalline structure of both layers. Annealing the samples increases the crystallite size but disrupts the continuity of the Sb2S3 film. Electrochemical and photoelectrochemical curves evidence the injection of holes from the light absorber Sb2S3 into the p-type NiO, but no significant photoinduced cathodic electron transfer to the electrolyte. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Atomic layer deposition; Photoelectrochemical cell; Sb2S3; NiO; Anodic aluminum oxide

Systematic increase of electrocatalytic turnover at nanoporous platinum surfaces prepared by atomic layer deposition - Assaud, Loic; Schumacher, Johannes; Tafel, Alexander; Bochmann, Sebastian; Christiansen, Silke; Bachmann, Julien (Journal of Materials Chemistry A, 2015)
We establish a procedure for the fabrication of electrocatalytically active, nanoporous surfaces coated with Pt and exhibiting a high geometric area. Firstly, the mechanism of the surface reactions between platinum(II) acetylacetonate and ozone is investigated by piezoelectric microbalance measurements. The data reveal that ozone oxidizes the metallic Pt surface to an extent which can exceed one monolayer depending on the reaction conditions. Proper reaction parameters yield a self-limited growth in atomic layer deposition (ALD) mode. Secondly, the ALD procedure is applied to porous anodic oxide substrates. The morphology and the crystal structure of the deposits are characterized. The ALD coating results in a continuous layer of Pt nanocrystallites along deep pore walls (aspect ratio 70). Thirdly, the Pt/TiO2 surfaces are shown to be electrochemically active in both acidic and alkaline media, in a way that qualitatively conforms to literature precedents based on Pt. Finally, we apply the anodization and ALD procedure to commercial Ti felts and demonstrate systematically how the electrochemical current density is increased by the large specific surface area and by the presence of the catalyst. Thereby, the catalyst loading, as well as its efficient utilization, can be optimized accurately. The preparative approach demonstrated here can be generalized and applied to the various electrocatalytic reactions of energy conversion device